Comparison of branched, fenestrated, and parallel strategies for endovascular treatment of thoracoabdominal aortic pathologies involving visceral regions - Ma, Xiaochen; Wu, Zhishi; Zhu, Guanglang; Guo, Mingjin; Li, Yongxin; Liu, Junjun; Liu, Mingyuan; Li, Youjin; Ye, Bo; Chen, Tao; Qi, Ming; Xiao, Hongyan; et al. (Frontiers in Cardiovascular Medicine, 2024)
Purpose: To compare the long-term efficacy of the parallel stent-graft (PSG) techniques , fenestrated stent-graft (FSG) techniques and branched stent-graft (BSG) techniques treating thoracoabdominal aortic pathologies. Materials and Methods: 291 patients with thoracic aortic aneurysm (TAA) and dissection (TAD) involving visceral arteries underwent PSG(n=85, 15 TAA and 70 TAD) or FSG (n=107, 47 TAD and 60 TAA) or BSG (n=99, 37 TAD and 62 TAA) were included in multiple centers from January 2015 to December 2022, and a total of 1108 visceral aortic branches were reconstructed. Results: The average reconstruction time of each visceral aortic branch for FSG, BSG, and PSG is 27.5±12.1 minutes,23.2±11.9 minutes, and 18.8±11.8 minutes, respectively (P<0.01).The rate of free from endoleak in last follow-up for FSG, BSG, and PSG is 86.9%,91.9%,and 60.0%, respectively. And the last follow-up patency rate for FSG, BSG, and PSG is 85.0%, 91.9%,and 94.1%, respectively. The average reconstruction price of each visceral aortic branch for FSG, BSG and PSG is 41.40 ± 3.22 thousand, 41.84 ± 3.86 thousand, and 42.35 ± 4.52 thousand, respectively (P=0.24). Conclusion: To treat the aortic pathologies involving visceral segment, BSG got lower endoleak rate and higher branch patency rate when compared with FSG and PSG techniques. And the expense of the BSG was comparable to other two techniques. Keywords: Aortic aneurysm, Aortic dissection, Endovascular repair, Visceral arteries, Branched stent-graft, Parallel stent-graft, Fenestrated stent-graft.